Survei minat dan motivasi klub bola basket Fast kecamatan Kaliwungu terhadap kegiatan olahraga bola basket pada masa pandemi Covid-19 - Melby Sabila Cahya; Galih Dwi Pradipta (Journal of Physical Activity and Sports (JPAS), 2021)
The purpose of this study was to determine the interest and motivation of members of the basketball club in the Kaliwungu sub-district towards basketball sports activities during the pandemic. The research method used was descriptive quantitative research method with the type of survey research method. The population of this study was the entire fast basketball team in Kaliwungu district using a sample saturated with as many as 20 club members. The results showed that the interest of the 20 athletes who became respondents obtained the highest results as many as 11 people (55%), the moderate category was 3 people (15%), the low category was 5 people (25%) and the very low category was 1 person (5). %), so it can be concluded that most of them have high interest. While the motivation of the 20 athletes who became respondents obtained results in very high categories as many as 3 people (5%), high category as 4 people (20%), medium category as many as 2 people (10%), and low category as many as 11 people (55%) ), so it is concluded that most of them have low motivation in doing sports, especially basketball during the Covid-19 pandemic. So it can be concluded that the interest of members of the fast basketball club during the Covid 19 pandemic is more due to the desire of members who want to keep exercising to maintain immunity body as well as physically so that they can avoid the existing outbreaks, while the motivation of members is still low because members still tend to worry about doing sports activities considering the outbreaks that still occur.